Synthesis and Antimicrobial Screening for Rhodanine Complexes of Iron, Copper and Zinc - Kshirsagar, Varsha; Gandhi, Sandhya; Dave Gautam, Mangla (Asian Journal of Chemistry, 2010)
In this paper, the synthesis and antimicrobial studies of rhodanine complexes with iron, copper and zinc are reported.